Sa hirap at ginhawa [soundrecording].
A dramatized counseling program on marital problems, wherein hosts Boots Anson Roa and Sylvia La Torre and alternating advisers, Fr. Ben Villote, Fr. Archie Guiriba, OFM, Msgr. Cesar Pagulayan, Fr. Rio Evangelista, SDB, and Fr. Victor Martelino, offer solutions to problems or insights into marital relationships.